Effectiveness of Oral Tranexamic Acid in the Treatment of Melasma: A Systematic Review - Zuniarto , Ahmad Azrul; TW, Siti Pandawangi; Kinanti, Vidya Putri (Journal La Medihealtico, 2025)
Melasma is a skin condition characterized by hyperpigmented patches, generally appearing on facial areas such as the cheeks, forehead, and upper lip. This condition is more common in women, especially during pregnancy or when using hormonal contraceptives. The factors that cause melasma include sun exposure, hormonal changes, and genetic factors. The purpose of this study is to examine the effectiveness and safety of the use of oral Tranexamic acid (TXA) in the treatment of melasma based on recent studies. The method used by literature search in journals published between 2022–2024 used keywords related to oral TXA and melasma. Studies that met the inclusion criteria were evaluated to compare the outcomes of oral TXA therapy based on dose, duration, and side effects. The results showed that oral TXA was proven to be effective in reducing the Melasma Area Severity Index (MASI) score with a dose of 500–1500 mg/day for 8–12 weeks. A significant decrease in MASI scores was achieved at week 12, showing consistent results across multiple studies. The most commonly reported side effects are gastrointestinal disorders, such as nausea and abdominal pain. Oral TXA does not cause serious side effects at doses up to 4 g/day. Tranexamic acid (TXA) in oral form is an effective and safe therapy in managing melasma. However, further research is needed to determine the ideal duration of treatment and strategies in preventing melasma recurrence.